A framework for analyzing monetary cost of database systems in the cloud - Chen, Changbing (2013)
In this paper, we propose to develop a framework to analyze the monetary cost of running database systems in the public cloud. The framework offers guidelines and methodologies in analyzing and estimating monetary cost of database systems. It consists of multiple components including categorizing database performance tuning knobs, benchmarking the price/performance of computation resources offered by the cloud provider, and building a monetary cost model. As a case study of our proposed framework, we conduct an in-depth study on two popular open-source database systems with respect to two cloud providers. We find that evaluating a query spans a wide range of monetary costs (with a difference up to 91%), and the experimental results demonstrate the accuracy of our monetary cost estimation.